2019
DOI: 10.2174/1381612824666181010150958
|View full text |Cite
|
Sign up to set email alerts
|

Should we Consider Lipoprotein (a) in Cardiovascular Disease Risk Assessment in Patients with Familial Hypercholesterolaemia?

Abstract: Background: Familial hypercholesterolaemia (FH) is a genetically determined lipid disorder, affecting 1 per 200-500 individuals in the general population. It is significantly and independently associated with an increased risk of Cardiovascular Disease (CVD), although it remains still an underrecognized and undertreated disease. Lipoprotein (a) [Lp(a)] is a low-density-lipoprotein (LDL)-like molecule, containing an additional protein, apolipoprotein (a). Objective: This review aims to present and discuss a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Interestingly, lipoprotein (a) (Lp[a]) concentrations, which are independently associated with increased risk of CVD, may also be increased in FH patients, compared to the general population [12]. In particular, the estimated prevalence of Lp(a) >30 mg/dl (>72 nmol/l) or >50 mg/dl (>120 nmol/l) is 29%-40.7% and 22%-29.4% of HeFH patients [13,14].…”
Section: Genetics Epidemiology and Diagnosismentioning
confidence: 99%
“…Interestingly, lipoprotein (a) (Lp[a]) concentrations, which are independently associated with increased risk of CVD, may also be increased in FH patients, compared to the general population [12]. In particular, the estimated prevalence of Lp(a) >30 mg/dl (>72 nmol/l) or >50 mg/dl (>120 nmol/l) is 29%-40.7% and 22%-29.4% of HeFH patients [13,14].…”
Section: Genetics Epidemiology and Diagnosismentioning
confidence: 99%
“…Individuals with heterozygous familial hypercholesterolaemia (HeFH) have almost 2.5-fold increased Lp(a) levels compared with controls 61 . It is suggested that Lp(a) has a binding affinity to LDLR but less than LDL due to apo(a) mask.…”
Section: Physiological Functions Of Lp(a)mentioning
confidence: 99%